Stereolithography 3D printing gyroid triply periodic minimal surface vitrified bond diamond grinding wheel - Zhaoqi Chen; Kehan Li; Ping Han; Yuetang Pan; Guoju Bai; Zijing Xia; Na Xiao; Pengyu Wang (Scientific Reports)
Abstract The pores of vitrified bond diamond grinding wheel play a key role in the grinding process. However, uneven pore distribution and low porosity affect the grinding performance of the wheel significantly. Stereolithography based additive manufacturing provides an effective method to fabricate vitrified bond diamond grinding wheels with a uniform distribution and an interconnected pore structure. The key to high-performance grinding wheel via stereolithography 3D printing lies in the preparation of the slurry with high solid loading, low viscosity and uniform stability. In this study, the dispersion and stability of vitrified bond and diamond slurries were investigated systematically. The effects of resin monomers, surface modifiers, and solid loading on the dispersion, rheological behavior and stability of slurries were studied in detail. Finally, an optimal vitrified bond and diamond slurry for stereolithography based additive manufacturing was obtained, and complex-shaped gyroid triply periodic minimal surface grinding wheel were fabricated. By grinding the SiC ceramics, the material removal rate, grinding temperature, and surface roughness were compared to those achieved using a conventional solid structure grinding wheel. The results show that the gyroid porous grinding wheel can achieve better surface roughness and lower the grinding temperature.